2015
DOI: 10.1111/trf.13136
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐effectiveness of Babesia microti antibody and nucleic acid blood donation screening using results from prospective investigational studies

Abstract: Universal PCR in endemic states is an effective blood donation screening strategy at a threshold of $50,000/QALY. Using a higher cost-effectiveness ratio, universal Ab/PCR is the most effective strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 26 publications
0
30
0
Order By: Relevance
“…Detection of window period infections would require methods other than serology, such as PCR or other direct parasite detection techniques, with the attendant relatively significant incremental cost. 38,39 However, even PCR is subject to limitations in sensitivity dependent on the target selected and on sample volume, which may vary between assays, and is capable of yielding false-negative results, in particular at low levels of parasitemia. 15 Volumes of whole blood utilized in published B. microti PCR protocols range from 200 mL to 2.0 mL, with corresponding analytical sensitivities ranging between 10 and 100 gene copies per PCR procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Detection of window period infections would require methods other than serology, such as PCR or other direct parasite detection techniques, with the attendant relatively significant incremental cost. 38,39 However, even PCR is subject to limitations in sensitivity dependent on the target selected and on sample volume, which may vary between assays, and is capable of yielding false-negative results, in particular at low levels of parasitemia. 15 Volumes of whole blood utilized in published B. microti PCR protocols range from 200 mL to 2.0 mL, with corresponding analytical sensitivities ranging between 10 and 100 gene copies per PCR procedure.…”
Section: Discussionmentioning
confidence: 99%
“…The economic impact assessment team noted that since 2014, three studies have been conducted on the cost effectiveness of B. microti screening with highly variable cost‐effectiveness results ranging from $54,000 to $83,000/quality‐adjusted life‐year (QALY) to $5.2 million/QALY and $8.8 million/QALY . Rather than undertake further cost‐effectiveness, we conducted an analysis of the number of infectious units that would be removed from the system through various testing methods and the cost of prevention.…”
Section: Assessing the Risk And Risk Management Options (Rbdm Stage 4)mentioning
confidence: 99%
“…Although their numbers may be low, these individuals show that PCR testing by itself will not always detect active infection. Accordingly, donor screening models have been proposed incorporating both serology and PCR [36,37]. …”
Section: Diagnostic and Screening Tests For Ttbmentioning
confidence: 99%
“…Each has arrived at different conclusions regarding the cost effectiveness of TTB screening for similar programs. Two studies found that effective programs could be devised that would cost less than the 1 million dollars per QALY threshold [37,48]. One of these found that universal donor antibody screening for B. microti in endemic areas of the US is the most promising approach while the other found that universal PCR in four endemic states would be most cost effective.…”
Section: Cost Effectiveness Of Screeningmentioning
confidence: 99%